ANALISIS KINERJA TENAGA KESEHATAN DI MASA PANDEMI COVID-19 DI BLUD RSU KABUPATEN BOMBANA - Asrul, Asrul; Tosepu, Ramadhan; Kusnan, Adius (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2021)
Human resource management in general is to obtain the highest level of employee development, harmonious working relationships among employees and effective integration of human resources or efficiency and cooperation goals so that it is expected to increase work productivity. This study aims to determine the relationship between advice and personal protective equipment with the performance of health workers at Bombana District General Hospital. This type of research is an observational analytic study using a cross sectional approach carried out at the BLUD RSU Bombana Regency involving health workers working in the BLUD RSU Bombana Regency with the status of ASN or honorary so that the total sample is 243 people. Data analysis used the chi-square test at a significant level of 5% (α=0.05), then processed using the SPSS version 16.00 application. The results showed that the performance of health workers was related to facilities (0.013) and personal protective equipment (0.008). It is expected that the hospital will be able to provide facilities according to service needs as well as personal protective equipment that is prepared flexibly according to the planning in the treatment room.